الدراسة الفيتوكيميائية والبيولوجية لمستخلصات النباتات: عين الحنش Lobularia libyca، السعدان Neurada procumbens، وكريشت الأرنب Launaea glomerata لمنطقة الوادي. - شلالبة, إيمان (University of Eloued جامعة الوادي, 2021)
تزخر منطقة شمال أفريقيا بغطاء نباتي متنوع وكثيف مما يجعلها محل دراسة، ويعتبر نبات السعدان، كريشت الأرنب، وعين الحنش من أكثر النباتات الرعوية التي تفضلها الإبل والغنم في ولاية الوادي جنوب شرق الجزائر. حيث أظهرت الدراسة السابقة لهذه النباتات ولنباتات من نفس جنسها أنها تحتوي على عدة مركبات فعالة وكانت لها عدة آثار تثبيطيه على عدة أنواع من الفطريات والبكتيريا، وأيضا تمتلك فعالية ضد العديد من الخلايا السرطانية. ومن هذا المنطلق أردنا معرفة مدى فعالية هذه النباتات التي لم يسبق دراستها في هذه المنطقة. بعد التحليل الأولي والكمي لهذه النباتات، أثبت احتوائها على كميات معتبرة من الفينولات والفلافونيدات، ومن ثم قمنا بعدة تحاليل كمية ونوعية. أظهرت النتائج احتواء النباتات على عدة عائلات كيميائية مهمة وعدة معادن بكميات معتبرة. كما اظهرت فعالية مضادة للأكسدة والتي أجريت بثلاث طرق (DPPH، CAT، ABTS)، وتمت مقارنة النتائج المتحصل عليها مع دراسات سابقة حديثة لنفس جنس النباتات من دول أخرى. وباستعمال الكروماتوغرافيا العالية الأداء LC-MS تم التعرف على عدة مركبات من عائلات كيميائية مختلفة، على الرغم من قلة المراجع حول هذه النباتات. أما فيما يخص القدرة المثبطة للخلايا السرطانية فقد تم اختبارها على كل من الخلايا الكبدية وخلايا القلون على مستوى المعهد القومي للخلايا السرطانية بمصر وكانت النتائج سلبية مع كل هذه النباتات. North Africa has a varied and dense vegetation cover, which makes it a subject of study, and Neurada procumbens, Launaea glomerata, Lobularia libyca are among the most preferred pastoral plants preferred by camels and sheep in EL-Oeud south east Algeria. Where the previous study of these plants and plants of the same genius showed that they contain several effective compounds and had several inhibitory effects on several types of fungi and bacteria and also have efficacy against many cancer cells. From this standpoint, we wanted to know the effectiveness of these plants that had not previously been studied in this area. After the initial and quantitative analysis of these plants, it was proved that they contain significant quantities of phenols and flavonoids, and then we carried out several quantitative and qualitative analyzes. The results showed that the plants contain several important chemical families and several minerals in significant quantities. It also showed antioxidant efficacy, which was conducted in three methods (DPPH, CAT, ABTS). The results obtained were compared with recent previous studies of the same sex of plants from other countries. Using high-performance chromatography (LC-MS), several compounds from different chemical families have been identified, although there are few references on these plants. As for the inhibitory ability of cancer cells, it was tested on both hepatocytes and colic cells at the level of the National Institute of Cancer Cells in Egypt, and the results were negative with all of these plants.
أطروحة دكتوراه في العلوم الدقيقة تخصص كيمياء
Keywords: نبات طبي، Neurada procumbens، Launaea glomerata، Lobularia libyca، فينولات، فلافونيدات، نشاط مضاد للأكسدة، الفعالية ضد الميكروبات، الفعالية ضد الخلايا السرطانية.; medicinal plant, Neurada procumbens, Launaea glomerata, Lobularia libyca, phenols, flavonoids, antioxidant activity, antimicrobial activity, activity against cancer cells.